Reprogramming of the mouse Nanog gene in amphibian oocyte extracts - Bereketoğlu, Sidar (2016)
To induce pluripotency in differentiated cells, it is necessary to remodel the epigenetic marks on the regulatory regions of pluripotency genes to enable their expression. The induction of Nanog expression is crucial for establishing pluripotency. However, the epigenetic mechanisms associated with the reprogramming of Nanog expression are not fully understood. In mammalian chromatin, epigenetic control of gene expression includes DNA methylation and histone modifications. In undifferentiated cells, regulatory regions of the pluripotency genes Nanog and Oct4 are demethylated and enriched with activating histone marks while being relatively depleted of repressive marks. One route to investigate mechanisms of cellular reprogramming is through treatment of cells with oocyte extracts from amphibians, such as Xenopus and axolotl. Previously, our lab demonstrated that a major difference between these extracts is that the axolotl oocyte can reprogram expression of the mammalian Nanog, while Xenopus oocyte cannot. In this study, I used extracts from oocytes of axolotl (AOE) and Xenopus (XOE), and focused on the mechanisms underlying the reversal of epigenetic marks in regulatory regions of the mouse Nanog gene during its reactivation. I demonstrated that AOE remodels the mouse somatic chromatin by increasing the level of 5hmC on both mouse Nanog enhancer and promoter sequences as well as adding the activating histone marks H3K27ac and H3K4me1 specifically to the Nanog enhancer. XOE was unable to induce these modifications. The expression of Nanog ortholog axNanog and histone variant H2A.Z in axolotl oocytes, but not in Xenopus oocyte, is likely to be one of the reasons for the differences. Indeed, I demonstrated the binding of axNanog and H2A.Z on the mouse Nanog gene in response to AOE, but not XOE treatment. Furthermore, my experiments have elucidated the sequence of chromatin remodelling events during oocyte extract reprogramming that begins with H2A.Z deposition at the Nanog enhancer which allows axNanog binding, followed by epigenetic alterations such as 5hmC, H3K27ac. Taken together, this study refines our understanding of the step-wise events necessary for remodelling of somatic cell chromatin and underlies the difference in the reprogramming capacity of different Amphibian oocytes.